The reimbursement decision speed for oncology new drugs in China and its determinant factors - Zhu, Xingyue; Chen, Yang (Frontiers in Public Health, 2023)
China has initiated the national price negotiation to improve access to innovative drugs. Learning the factors that contributed to the time gap from marketing authorization to reimbursement conduces to more clarity on the decision making, but which remains under-researched in China. Using data from the Listed Drug Database by the China drug agency, we analyzed 186 oncology new drug approvals marketed before 30 Jun, 2022. We found that, the time gap between marketing authorization and reimbursement has decreased in recent years. The domestic new drugs had higher probability of being adopted by the China public payer, in comparison to drugs developed by foreign companies. Furthermore, New Drug Applications receiving regular review pathway were more likely to be reimbursed as opposed to those approved under the conditional approval pathway. These findings indicate that the China payer is actively working towards improving access to new oncology drugs. The faster reimbursement decision speed for domestic drugs might be attributed to their pricing advantages and the regulator's efforts to stimulate innovation in the domestic pharmaceutical industry. However, concerns for uncertain evidence of drug benefits can affect the reimbursement decision making, which suggests the delicate tradeoff between drug accessibility and risk involved in the reimbursement process.